Exploring the neurobiological correlates of psilocybin-assisted psychotherapy in eating disorders: a review of potential methodologies and implications for the psychedelic study design - Elena Koning; Cristiano Chaves; Ryan H. Kirkpatrick; Elisa Brietzke (Journal of Eating Disorders)
Abstract Eating disorders (EDs) are a group of debilitating mental illnesses characterized by maladaptive eating behaviors and severe cognitive-emotional dysfunction, directly affecting 1–3% of the population. Standard treatments are not effective in approximately one third of ED cases, representing the need for scientific advancement. There is emerging evidence for the safety and efficacy of psilocybin-assisted psychotherapy (PAP) to improve treatment outcomes in individuals with EDs. However, the limited knowledge of the neurobiological mechanisms underlying the therapeutic effects of PAP restricts the ability to confirm its clinical utility. This narrative review presents an overview of methodologies used to elucidate the pathophysiological mechanisms of EDs or the effects of psilocybin that could be employed to probe the neurobiological correlates of PAP in EDs, including magnetic resonance imaging and molecular neuroimaging techniques, electrophysiological approaches, and neuroplasticity markers. Finally, the implications of these methodologies are described in relation to the unique features of the psychedelic study design, challenges, limitations, and future directions to advance the field. This paper represents a valuable resource for scientists during study conceptualization and design phases and stimulates advancement in the identification of effective therapeutic interventions for EDs.